Diseño e implementación de una máquina amasadora de harina en el sector de Yugsiloma - Martínez Paca, Darwin Vinicio (2018)
This thesis aims to reduce the time of knead through the implementation of flour knead machine 25 kg in the Women's Association Pastry chefs Yugsiloma, Latacunga city, in order to reduce the times of kneading and decreased over the course of the effort in the production process. The flour kneading machine was built to be operated in an intuitive, ergonomic way, besides it will solve the kneading capacity and production process time, it is important to mention that different types of kneaders were taken into account, of which it selected the horizontal kneader with which it was governed for the design and construction of the kneader, in addition a time control system was installed in the kneading allowing the machine to turn off in an automatic way. For the construction of the kneading machine in the pot AISI 304 stainless steel was used because its properties are suitable for the food production obtaining a product suitable for the human consumption, for the structure the stainless steel AISI 430 was used by the anti-corrosive properties prevent the steel from rusting. The transmission system was carried out by means of lifters and catalinas which allows to reduce the revolutions per minute of the motor at the same time maintaining the force and the rotation of the constant arms ensuring that the gluten is optimal. The kneading machine is environmentally friendly because noise and vibrations meet the established standards of 45db without affecting the working environment, allowing other work to be done while the machine is running. It also has a pot that rotates 90 degrees with respect to its axis facilitating the extraction of gluten in a simple way without much effort.